2019
DOI: 10.1111/ddg.13776
|View full text |Cite
|
Sign up to set email alerts
|

Trichophyton mentagrophytes – a new genotype of zoophilic dermatophyte causes sexually transmitted infections

Abstract: Summary Background A new genotype of the zoophilic fungal species Trichophyton (T.) mentagrophytes was recently described in two studies. It was isolated from three patients who had visited Southeast Asia and one patient who had visited Egypt. In contrast to these studies, we have observed a number of cases with the dimensions of an epidemic outbreak. Patients and methods At the University Hospital Charité Berlin, 43 patients, mostly suffering from highly inflammatory, painful and persistent infections of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 30 publications
2
35
0
3
Order By: Relevance
“…Recently, some investigations supported by molecular procedures indicated that ITS genotypes in the TMTISG still may be correlated with clinical pictures, geographic locations and antifungal resistance. [7][8][9] The question of association between particular TMTISG genotypes and clinical manifestations of infections by respective strains has not been addressed by statistical methods. Also, comprehensive analysis of geographic distribution of TMTISG genotypes is lacking.…”
Section: T Mentagrophytes/t Interdigitale Species Group (Tmtisg)mentioning
confidence: 99%
“…Recently, some investigations supported by molecular procedures indicated that ITS genotypes in the TMTISG still may be correlated with clinical pictures, geographic locations and antifungal resistance. [7][8][9] The question of association between particular TMTISG genotypes and clinical manifestations of infections by respective strains has not been addressed by statistical methods. Also, comprehensive analysis of geographic distribution of TMTISG genotypes is lacking.…”
Section: T Mentagrophytes/t Interdigitale Species Group (Tmtisg)mentioning
confidence: 99%
“…Both in-house tests and commercially available test systems (kits) may be used for this purpose [50][51][52]. In the aforementioned cases, the disease course correlated with the molecular findings [53,54]. Thus, molecular techniques are significantly more rapid (24-48 hours versus 2-6 weeks for culture-based methods) and sensitive than KOH preparation and culture [43].…”
Section: Molecular Methods For Pathogen Identification In Tinea Capitismentioning
confidence: 99%
“…In two other patients, the dermatophyte was detectable by PCR-based methods for several weeks, whereas cultures remained negative. In the aforementioned cases, the disease course correlated with the molecular findings [53,54]. Further comparative studies should be conducted in order to determine whether -apart from enabling more rapid pathogen identification -PCR-based methods are also suitable for treatment monitoring in patients with TC.…”
Section: Molecular Methods For Pathogen Identification In Tinea Capitismentioning
confidence: 99%
“…If neither of the two variants was detected, a pan-dermatophyte-specific PCR and external sequencing (LGC Genomics GmbH, Berlin, Germany) followed for species differentiation. For this PCR, the ITS5 primer [ 4 ] was used in combination with a pan-dermatophyte-specific reverse primer [ 5 ] to amplify the entire ITS1 region. The annealing temperature was 56 °C.…”
Section: Methodsmentioning
confidence: 99%